Comparative Advantages with Product Complexity and Product Quality - Ulrich Schetter (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We analyze the interplay between product-intrinsic complexity and endogenously chosen product quality in international trade. Our work reveals a novel mecha-nism that can explain a rich set of empirical observations: (1) how specialization within products on quality can equalize comparative advantages across products,(2) why poor countries do not export a broad range of products nonetheless, and (3) why the share of products for which this is the case tends to be decreasing over time. Our theory motivates the use of a censored regression model to esti-mate the link between a country's GDP per capita and the quality of its exports. Following this empirical strategy, we find a much stronger relationship than when using OLS, in line with our theory.
Keywords: F11; F14; F19; 330